2016
DOI: 10.3389/fpsyg.2016.00460
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year-Old Preschoolers’ Sharing is Influenced by Anticipated Reciprocation

Abstract: Whether children share in anticipation of future benefits returned by a partner is an interesting question. In this study, 5-year-old children and an adult partner played a sharing game, in which children donated first and the partner donated afterward. In Experiment 1, the partner’s resources were more attractive than the child’s. In the reciprocal condition, the child was told that s/he would be a recipient when the partner played as a donor. In the non-reciprocal condition, however, the child was told that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 58 publications
0
24
0
Order By: Relevance
“…It is very common in developmental research that subjects are asked to divide actual resources between themselves and anonymous others (Blake and Rand, 2010; Gummerum et al, 2010; Engelmann et al, 2013; Xiong et al, 2016). This resource-allocation paradigm has many methodological advantages.…”
Section: Discussionmentioning
confidence: 99%
“…It is very common in developmental research that subjects are asked to divide actual resources between themselves and anonymous others (Blake and Rand, 2010; Gummerum et al, 2010; Engelmann et al, 2013; Xiong et al, 2016). This resource-allocation paradigm has many methodological advantages.…”
Section: Discussionmentioning
confidence: 99%
“… 3 Interestingly, an earlier study ( Benenson et al, 2007 ) had found that DG allocations made to a classmate increased with age among children between 4 and 9 years of age, particularly among high SES children, although this study did not assess ToM. Likewise, studies have shown that found that preschoolers ( Fujii et al, 2015 ) contributed more in the DG played with strangers only when they were being watched by an experimenter (see Takagishi et al, 2015 , for similar results with elementary school age boys), or when there is an opportunity for the other player to reciprocate ( Xiong et al, 2016 ). Similarly, Leimgruber et al (2012) found that 5 years-old were more likely to share only when they knew that the recipient was aware of their donation options.…”
mentioning
confidence: 86%
“…This finding lends credibility to the use of HRV coherence as an indicator of vagal tone. Another advantage of measuring the HRV coherence ratio is that it likely serves as an indicator of the cardiorespiratory coupling (cardiorespiratory phase synchronization) that occurs during deep sleep and may help facilitate homeostasis between the ANS and cardiopulmonary systems (Tobaldini et al 2013 ; Cabiddu et al 2012 ; Penzel et al 2016 ; Jerath et al 2014 ; Garcia et al 2013 ). Because HRV coherence can be achieved via behavioral interventions that implement a resonant frequency breathing protocol (i.e., HRV biofeedback) (Lehrer et al 2000 ; Garcia et al 2013 ; Wheat and Larkin 2010 ; Lehrer and Gevirtz 2014 ), the authors speculate that, if the findings of the current study are confirmed, HRV biofeedback may help facilitate shift work adaptation via increases in HRV coherence, which have been associated with improvements in cognitive performance and sleep, as well as reductions in stress, anxiety, and depression (Goessl et al 2017 ; Thayer et al 2009 ; Lehrer 2018 ; Lehrer and Gevirtz 2014 ; Morgan and Mora 2017 ; Sakakibara et al 2013 ), and are all conditions that are commonly encountered among shift workers.…”
Section: Discussionmentioning
confidence: 99%
“…Results from interventions targeting HRV coherence suggest that it may alleviate adverse impacts encountered among shift workers by facilitating improvements in cognitive performance and sleep, and by reducing stress, anxiety, and depression (Goessl et al 2017 ; Thayer et al 2009 ; Lehrer 2018 ; Lehrer and Gevirtz 2014 ; Morgan and Mora 2017 ; Sakakibara et al 2013 ). Additionally, the restorative properties of deep sleep are considered to be related to the parasympathetic dominance, resonant frequency breathing, and cardiorespiratory coupling that occur during non-rapid eye movement (NREM) and slow-wave sleep (Tobaldini et al 2013 ; Cabiddu et al 2012 ; Penzel et al 2016 ; Jerath et al 2014 ). However, to the authors’ knowledge, human HRV coherence has never been quantified in a non-experimental setting during either work or sleep periods.…”
Section: Introductionmentioning
confidence: 99%